Clinical analysis of 40 cases of external cephalic version without anesthesia. Issue 1 (January 2021) - Zhi, Zheng; Xi, Lin
Objective: This study aimed to investigate the success rate, complications, and success-related factors of external cephalic version (ECV) of singleton breech pregnancies after 37 gestational weeks without anesthesia. Methods: We studied 40 singleton breech pregnancies in women who underwent ECV without anesthesia after 37 gestational weeks from October 2018 to March 2020. On the basis of success of ECV, the women were divided into two groups of the successful group and the failed group. Various factors were analyzed to determine those that affect the success of ECV. Results: Of the 40 attempts of ECV, 24 (60.0%) were successful and 16 (40.0%) failed. With regard to success-related factors, parity was significantly different between the two groups, with more multiparous women in the successful group than in the failed group. However, none of the other factors were significantly different between the groups. Fetal outcome was good in all of the cases. Ultimately, 3 cesarean sections were performed in the successful group and 16 were performed in the failed group. Conclusions: ECV of breech presentation after the 37th week of pregnancy without anesthesia is an effective and relatively safe alternative, and can effectively reduce the cesarean section rate.